Notary’s Role and Authority on the Issue of Interreligious Marriage in Surabaya City - Tjajaindra, Phinawati; Djaja, Benny (Interdisciplinary Social Studies, 2023)
Background: Interfaith marriages occur in Indonesia, one of which is in the city of Surabaya. Once the marriage is valid, it must be reported to the Civil Registry Occupation Service and issue an Ottentic Deed. Authentic Deeds that are considered official must comply with the provisions of Article 1868 of the Civil Code. What is meant by official in this article is a notary. This is regulated in Article 1 Article 15 paragraph 1 of UUJN. The Notary Department plays an important role in the ratification of Marriage Certificates both of the same religion and different religions in Indonesia. Aim: The author's purpose in creating this journal is to find out how interfaith marriage relations in Indonesia with the civil law of interfaith marriage and the hierarchy of laws and regulations related to interfaith marriage. Method: The research method that researchers use is juridical normative with qualitative research. Findings: The result of this study is that the Interfaith Marriage Agreement in Indonesia based on Law No. Article 16 of 2019 concerning Marriage clarifies the role of religion in marriage and the confirmation of faith, stating that a valid marriage is a marriage carried out according to the laws of each religion and its adherents. The state leaves the assessment of the validity of marriage to the religion and beliefs of the people concerned.  Thus, Law Number 16 of 2019 concerning Marriage is a standard that regulates not prohibits. The state does not prohibit individuals from interfaith marriages.